KONSEP PENDIDIKAN SAINS MENURUT AL-RĀZĪ (Tela'ah Terhadap Tafsir Mafātīḥ al-Ghayb) - Muhammad Azhari (Universitas Islam Negeri Ar-Raniry, 2013)
This article discusses educational science based on Mafatihul Tafsir perspective, al-Rāzī work. The book of Mafātiḥ al-Ghayb contains the theory about Islamic science and has its relevance to the modern science. In the view of Al-Rāzī, modern science and Islamic science has a strong correlation, and even both were born on the same outlook of oneness. Islamic history has proven that the Qur'an was separated from science and Muslim turned to backward. Great scholars of Islam during al-Rāzī agreed that all science disciplines either existing or none, old or new, which is controlled by the Muslims or not, everything should lead to the unity of Allah. If not, the science of human contrary to the common sense, and contrary to the Qur'an or Hadith where it must be rejected its truth.